On Being Lutheran In A Religiously Plural World - Ingram, Paul O. (Dialog, 2007)
For those of us who are self-consciously Lutheran, the reality of contemporary religious pluralism engenders important theological questions. The thesis of this essay is that “being Lutheran” within the context of contemporary religious pluralism requires the creation of “Lutheran identity” that is pluralistic in structure, while simultaneously avoiding either theological exclusivism or theological inclusivism. The implications of this thesis are that (1) dialogue with the religious traditions of the world is of primary importance for thinking Lutherans, and (2) the church's witness and mission needs to be reconfigured in light of the practice of interreligious dialogue.